Incremental Contributions of Parental Acceptance and Family Functioning to Social-Emotional Skills of Children with Physical and Sensory Disabilities - Jimny Hilda Fauzia (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
Social-emotional skills are essential for the psychological adjustment and social participation of children with physical and sensory disabilities. Family-related factors, particularly parental acceptance and family functioning, have been associated with children's social-emotional development, yet their relative contributions remain unclear. This study examined the incremental contribution of family functioning beyond parental acceptance in predicting social-emotional skills among children with physical and sensory disabilities. A cross-sectional survey was conducted with 132 parents of elementary school children with hearing, visual, physical, and speech disabilities recruited through special schools, inclusive schools, therapy centres, and online communities in Indonesia. Social-emotional skills, parental acceptance, and family functioning were measured using adapted versions of the Elementary School Students' Social and Emotional Skills Survey, the Parental Acceptance-Rejection Questionnaire (PARQ), and the Family Assessment Device (FAD), respectively. Hierarchical multiple regression was performed by entering parental acceptance in the first block, followed by family functioning in the second block. Parental acceptance significantly predicted children's social-emotional skills when entered independently; however, its unique contribution became non-significant after family functioning was added to the model. Family functioning contributed an additional 4.9% of the explained variance and remained a significant predictor in the final model (β = .305, p = .010), with the overall model explaining 8.4% of the variance in children's social-emotional skills (R² = .084). These findings indicate that family functioning provides incremental explanatory value beyond parental acceptance.